2019
DOI: 10.1021/acsomega.8b02084
|View full text |Cite
|
Sign up to set email alerts
|

Improved Corrosion Resistance of Steel in Ethanol Fuel Blend by Titania Nanoparticles and Aganonerion polymorphum Leaf Extract

Abstract: A porous and low-density protective film on a steel surface in the corrosive environment can undergo deterioration even in the presence of organic inhibitors due to infiltration of aggressive ions into the pinholes and/or pores. This phenomenon is related to the localized corrosion that takes place even in the presence of an optimal concentration of organic corrosion inhibitors in the given medium. To overcome this issue, we have designed an organic protective film on a steel surface with the help of titania n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…On the other hand, the benefit of NP addition can be explained from the Bode plots of Figure S4 where an improvement (in both height and width) for the medium-frequency range, which corresponded to the processes within the protective organic film (and its integrity), was found. This could indicate that the porous organic film had its pores filled, similar to what Hoai Vu et al have achieved . The first observation from XPS is the consolidated single corrosion product, similar to a passivated surface.…”
Section: Results and Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…On the other hand, the benefit of NP addition can be explained from the Bode plots of Figure S4 where an improvement (in both height and width) for the medium-frequency range, which corresponded to the processes within the protective organic film (and its integrity), was found. This could indicate that the porous organic film had its pores filled, similar to what Hoai Vu et al have achieved . The first observation from XPS is the consolidated single corrosion product, similar to a passivated surface.…”
Section: Results and Discussionsupporting
confidence: 74%
“…This could indicate that the porous organic film had its pores filled, similar to what Hoai Vu et al have achieved. 27 The first observation from XPS is the consolidated single corrosion product, similar to a passivated surface. The PD results can also confirm this with its obvious anodic passive region from −500 to −400 mV Ag/AgCl .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In contrast, electrochemical methods, such as electrochemical impedance spectroscopy (EIS) and polarization characteristic measurements, have higher demands on the instrumental equipment compared with the gravimetric methods, but they provide much more corrosion information in a much shorter period . Moreover, both the gravimetric and electrochemical methods make it possible to evaluate the efficiency of green corrosion inhibitors. …”
Section: Introductionmentioning
confidence: 99%
“…Also, the influence of the addition of TiO 2 nanoparticles on the inhibition of the natural steel corrosion inhibitor based on the extracts , in an environment of EGBs was tested . The study demonstrated the beneficial effect of these nanoparticles on inhibition …”
Section: Introductionmentioning
confidence: 99%